(untitled) (Journal of the College of Basic Education, 2025)
The aim of the research is to identify the effect of the STAD strategy on mathematical readability among fifth-grade primary school students. The research sample consisted of (49) students from the fifth grade during the second semester of the academic year (2024–2025), from Al-Imam Al-Baqir Primary School for Boys affiliated with the General Directorate of Education in Maysan, which was intentionally selected. The sample was divided into two groups: (25) students in the experimental group (Class A), which was taught according to the STAD strategy, and (24) students in the control group (Class B), which was taught using the traditional method The two groups (experimental and control) were statistically equalized in the following variables: intelligence, chronological age (in months), previous achievement in mathematics, prior knowledge in mathematics, and parents’ educational level.The research tool— a mathematical readability test— was constructed, consisting of (14) texts. Using the Cronbach’s Alpha formula, the reliability coefficient was found to be good, with a value of(0.85). After completing the experiment, the mathematical readability test was administered to both research groups. The results were analyzed using statistical methods, including the independent samples t-test within the SPSS software, version 25. The results showed a statistically significant difference at the (0.05) level between the mean scores of the experimental group and the control group in favor of the experimental group. In light of the results, several conclusions were drawn, including that teaching fifth-grade students according to the STAD strategy had a positive effect on mathematical readability compared to the traditional method. Several recommendations and suggestions were made, the most important of which are: working to improve mathematical readability by encouraging students to read mathematics aloud, urging mathematics teachers to pay attention to mathematical language, and conducting a comparative study between the STAD strategy and other cooperative learning strategies to examine their effects on mathematical readability